2019
DOI: 10.3389/fmats.2019.00323
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Durability of PLA Bionanocomposite Fibers Under Hygrothermal Conditions

Abstract: Hygrothermal aging of neat poly(lactic acid) (PLA), PLA/microcrystalline cellulose (MCC), and PLA/cellulose nanowhiskers (CNW) fibers prepared by melt-spinning process was investigated at 95% relative humidity (RH) and two temperatures, i.e., 45 and 60 • C. PLA bionanocomposite fibers were melt compounded at filler content of 1 wt% in the presence of PLA-grafted-maleic anhydride (PLA-g-MA) (7 wt%) used as compatibilizer. The influence of the type of cellulosic filler and the temperature on the hydrolytic degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The water diffusion coefficients ( D ) at 65°C, obtained from the best fit of experimental data according to Equation ), are similar and their values are estimated to 9.0 × 10 −7 and 9.3 × 10 −7 cm 2 h −1 for Cast PHBV and C‐PHBV/3C30B bionanocomposite, respectively. The literature [ 38,41–42 ] reported that the capacity of water absorption and its rate of diffusion in nanocomposites depending on various factors such as: specific surface area of the clay, micro vide existing in the polymer/clays interfaces, free volume in polymer matrix, the tortuosity of water diffusion into the polymeric matrix, molecular relaxation and polymer matrix crystallinity. The higher amount of water absorption in the PHBV bionanocomposite is related to the hydrophilic nature of organoclays (C30B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water diffusion coefficients ( D ) at 65°C, obtained from the best fit of experimental data according to Equation ), are similar and their values are estimated to 9.0 × 10 −7 and 9.3 × 10 −7 cm 2 h −1 for Cast PHBV and C‐PHBV/3C30B bionanocomposite, respectively. The literature [ 38,41–42 ] reported that the capacity of water absorption and its rate of diffusion in nanocomposites depending on various factors such as: specific surface area of the clay, micro vide existing in the polymer/clays interfaces, free volume in polymer matrix, the tortuosity of water diffusion into the polymeric matrix, molecular relaxation and polymer matrix crystallinity. The higher amount of water absorption in the PHBV bionanocomposite is related to the hydrophilic nature of organoclays (C30B).…”
Section: Resultsmentioning
confidence: 99%
“…The overall decrease in T m is ascribed to the formation of short chain segments with lower molecular weight due to chain scission through hydrolysis, and the consecutive formation of imperfect crystals. Thus, the lower melting peaks correspond to imperfect crystallites formed after melting and recrystallization of aged samples, while the higher melting peaks correspond to more perfect crystals that melt at higher temperature [42,45] . Table 2 also shows a slight decrease of T c and X c with increasing exposure time.…”
Section: Samplesmentioning
confidence: 99%
“…For the melt-spun fibres with any local low-quality integration (i.e., clustering), the high temperature presumably leads to merging and diffusion of rosin inside the PE bulk. Contrary to all of the PE fibres, PLA fibres simply re-deform at 70 °C due to the low glass transition temperature ( = 55 °C [ 39 ]) and hydrolysis at temperatures of 45–60 °C in hydro-thermal conditions [ 16 ]. After the temperature reaches the washing temperature of 70 °C in PLA, the filaments have already deformed and do not represent fibres and cannot be tested as filaments.…”
Section: Results and Analysismentioning
confidence: 99%
“…The results about the poor performance at 60 °C (lost integrity) are strongly supported by the current literature [ 43 ]. For a cellulose-based filler, Aouat et al reported that it was not possible to even determine Young’s modulus after nine days of conditioning at 60 °C independent of the dosage of natural additives (cellulose) [ 16 ]. In summary, when noting the results of antibacterial response of the fibres modified by the selected Ag-containing additive, the selected PLA (grade) is less preferred polymer basis for polyfilament melt-spinning with rosin compared to the developed PE compounds with rosin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation